Anglican Recognition of Presbyterian Orders: James Cooper and the Precedent of 1610 - Young, Douglas MacMurray (Studies in church history, 1996)
One of the foremost advocates of union between the Anglican and Presbyterian Churches at the beginning of this century was James Cooper, Regius Professor of Ecclesiastical History in the University of Glasgow from 1898 to 1922. Cooper was the best-known representative within the Church of Scotland of the Scoto-Catholic or high-church movement which was expressed in the formation of the Scottish Church Society in 1892. One of the ‘special objects’ of the Society was the ‘furtherance of Catholic unity in every way consistent with true loyalty to the Church of Scotland’. The realization of catholic unity led high churchmen to seek what Cooper termed a ‘United Church for the British Empire’ which would include the union of the Church of Scotland and the Church of England. This new unity would require a reconciliation of differences and the elimination of diversities: on the one hand an acceptance of bishops by the Scottish Presbyterians; on the other an acceptance of the validity of Presbyterian orders by Episcopalians and Anglicans.